Assessment of the transformative potential of interventions in addressing coastal and marine plastic pollution in Norway: A literature review - Amirova, Natalya; Riechers, Maraja; Richter, Isabel (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Marine plastic pollution is a pressing and wicked problem. Hence, to tackle plastic pollution, the focus should be on systemic solutions and achieving societal transformation. Yet, how societies can effectively initiate such transformation is not well understood. This study examines implemented interventions to address coastal and marine plastic pollution in Norway, with a special focus on the interventions’ transformative potential. Following PRISMA guidelines, a total of 52 eligible interventions from 39 publications were identified and categorized according to the leverage points (LP) perspective. The findings reveal that the majority of interventions (61.5%, n = 32)—such as recycling, cleanups, monitoring, and charges for plastic use—address system parameters and system feedbacks and indicate a predominant focus on interventions that are relatively easy to implement but possess limited transformative potential. Three interventions with transformative potential, addressing system intents, were identified. To further analyse interventions’ transformative potential, this article integrated societal intrinsic and extrinsic values perspective from social psychology. Drawing on an analysis of LP and values perspectives, we presented a definition of a transformative intervention to integrate two disciplinary viewpoints; we also outlined several transformative interventions across different societal levels. The contribution of this study is to enhance understanding and encourage research on concrete interventions with transformative potential and transformative interventions.
Keywords: Pollution; Marine Monitoring; Ocean; Marine Environment; Social System; Norway